Hipparion in Luotuo Hill, Dalian, and evolution of latest Hipparion in China. (30th July 2021) - Sun, Boyang; Liu, Sizhao; Song, Yayun; Liu, Yan; Wang, Shiqi; Shi, Qinqin; Zhang, Fengjiao; Wang, Yuan
Abstract: Some Hipparion specimens from Jinyuan Cave, Luotuo Hill, Dalian is reported in the present research. The specimens from Pleistocene strata are large-sized ones include two forms. One has complicated folds in fossettes, pli caballine with two or more branches, elongated oval protocone, has been identified as Hipparion ( Proboscidipparion ) sinense ; the other has less complicated fossette folds, single pli caballine, extremely elongated protocone, has been identified as Hipparion ( Plesiohipparion ) shanxiense. The small-sized mandible material and Mc III from Pliocene layer are identified as Hipparion ( Proboscidipparion ) pater and Hipparion sp. respectively. The known late taxa of Hipparion in China are revised in the present research. The most significant concept about late Hipparion in China, Sivalhippus Complex is reviewed. The phylogenetic discussion based on recent morphological recognition indicated that subgenus Plesiohipparion is actually close to subgenus Sivalhippus . Subgenus Proboscidipparion is closer to H. dermatorhinum rather than Plesiohipparion and Sivalhippus . Hipparion specimens were yielded from three layers in Jinyuan Cave deposition, which could be correlative with faunae respectively in early, middle and late stages in early Pleistocene in China. Early Pleistocene Hipparion, such as H. sinense and H. shanxiense often occurred in Equus fauna. They exhibit significance on biostratigraphy and could be regarded as a mark for the beginning of Quaternary, like Equus .